DETERMINATION OF PHENOLOGICAL AND POMOLOGICAL CHARACTERISTICS OF SOME APPLE CULTIVARS IN NİĞDE-TURKEY ECOLOGICAL CONDITIONS - F. Bozbuğa; L. Pırlak (Journal of Animal and Plant Sciences, 2012)
The aim of this study was to define phenological and pomological characteristics of some apple varieties grafted on dwarf and semi-dwarf rootstocks. The experiment was conducted at Sazlıca/Niğde on the orchard of private sector during 2006 and 2007. In this experiment, bud swelling, bud breaking, begin of blooming, full blooming, last blooming and harvesting data of Galaxy, Mondial Gala, Red Chief, Super Chief, Oregon Spur, Scarlet Spur, Early Red One, Granny Smith and Fuji (Standard type) apple varieties were observed. The results from our research shown that, full blooming date was 20 April- to 10 May, fruit harvesting was between 20 August and 13 October.  Average weight of the fruits was 144.6 g (Galaxy Gala) to 216.3 g (Fuji). The average width of the fruits was 70.1 mm (Galaxy Gala) to 81.7 mm (Fuji). The average height of the fruits was 57.6 mm (Mondial Gala) to 70.3 mm (Granny Smith). The fruit index was 1.13 (Early Redone) to 1.22 (Galaxy Gala, Mondial Gala). The number of seeds was 6.5 (Galaxy Gala) to 9.3 (Granny Smith). The content of soluble solids in the fruits was 12.2 % (Granny Smith) to 16.5 % (Fuji). The starch amount was 1.82 (Early Red One) to 3.00 (Mondial Gala). As a result, according to phenological, pomological properties and yield results of investigated varietes for the conditions of Niğde, the cultivation of Galaxy Gala, Red Chief, Oregon Spur, Granny Smith and Fuji should recommend.
Keywords: Apple Varieties; Phenological and Pomological Properties; Niğde Province.